Quantifying pollutant loading from channel sources: Watershed-scale application of the River Erosion Model. (15th March 2019) - Lammers, Roderick W.; Bledsoe, Brian P.
Abstract: Phosphorus and fine sediment pollution are primary causes of water quality degradation. Streambank erosion is a potentially significant source of fine sediment and particulate phosphorus to watersheds, but it remains difficult to quantify the magnitude of this loading. A new, easily applied, watershed scale model was used to simulate the potential for future phosphorus and sediment loading from channel erosion in two watersheds: Big Dry Creek, Colorado and Lick Creek, North Carolina. The projected magnitude of loading for phosphorus is about an order of magnitude higher in Big Dry Creek compared to Lick Creek (∼280 kg/yr and ∼50 kg/yr, respectively), while sediment loading results are similar (∼950 ton/yr). In both watersheds, model results suggest that channel erosion will not contribute a significant amount of phosphorus to the watershed (∼1–4% of historic watershed total from all pollutant sources) but will contribute a large amount of sediment (30–100% of historic watershed total). Uncertainty in these estimates is high, but quantifying confidence in model projections is important for understanding and using model results. Importantly, modeling shows no decrease in loading over the 40-year model time frame in either watershed, suggesting that the channels are not adjusting to a new stable state and erosion will continue to be a pollutant source. Lick Creek model results are sensitive to upstream sediment supply while Big Dry Creek's are not, reinforcing the importance of considering alterations to both the hydrologic and sediment regimes when analyzing potential channel changes — at least in vertically active channels. This new modeling approach is useful for estimating historic and future phosphorus and sediment loading from channel erosion, an important first step in effective management to improve water quality. Graphical abstract: Image 1 Highlights: Channel erosion and pollutant loading was modeled in two watersheds. Channel erosion is not expected to be a significant source of phosphorus. Channel erosion will likely be a significant source of fine sediment. Uncertainty is high but relative magnitudes of contributions are clear.